Biomechanics of Injury and Prevention - Fan, Yubo.; Wang, Lizhen (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book summarizes the recent advancements for biomechanics of injury and prevention in mechanism, application and developing frontiers. Biomechanics plays an important role in achieving safety, health, comfort, and a high quality of life by revealing injury mechanism and providing prevention methods. The book covers injury and prevention to the entire human body, from head to toe, including injury and prevention in sports, traffic, accident, clinic and so on. In addition, bionics prevention method inspired by woodpecker is also introduced. The book provides the reader with not only the mechanism of injury but also the advanced injury diagnosis, treatment, and prevention devices based on biomechanics.
1 Introduction -- 2 Biomechanical study on injuries of human head-neck complex -- 3 Resist mechanism of woodpecker's head and neck injury -- 4 Biomechanical study on the mechanism of eye injuries -- 5 Biomechanics of the optic nerve -- 6 The mechanism of pulsatile tinnitus and treatment -- 7 Biomechanics of lower limb injuries during landing -- 8 The biomechanical study of half-squat parachute landing and injuries prevention -- 9 Biomechanical study on injury and treatment of human knee joint -- 10 The protective effect of insole on foot injury -- 11 Biomechanics of magnesium-based implant during tissue repair -- 12 Image-based finite element modeling for the descriptions of bone failure behaviors -- 13 Weightless musculoskeletal injury and protection -- 14 Study on the strength of manual work -- 15 The ergonomic system for the partial pressure suit.
Keywords: Biotechnology; Biomechanics; Biophysics; Biotechnology; Biomechanics; Biophysics